2018
DOI: 10.1080/01658107.2018.1536998
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Eye and Cranial Movements Triggered by Examination in People with Functional Neurological Disorder

Abstract: The diagnosis of functional neurological disorder (FND) relies on the demonstration of positive symptoms and signs, as supported by recent changes in DSM5. We recorded the findings of routine clinical eye movement assessment in 101 consecutive new patients with FND. Clinical examination triggered facial and eye movement disorders in 46% of patients, all with positive characteristics of functional movement disorder. These are useful as supporting features in making a positive diagnosis of FND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…We had 4 patients who had abnormal movements related to the eyes: one patient each of bilateral ptosis, blepharospasm, eyebrow dyskinesia, and bilateral 'painful' eyelid myoclonus. In a large series of 101 patients clinical examination triggered facial and eye movement disorders in 46% of patients, but, this phenomenon was not observed in any of our patients [15]. In the same vein, Stone et al in 2010 reported a case with recurrent episodes of right "pseudoptosis" with contraction of orbicularis oculis and oris which gave an impression of right facial weakness with unilateral photophobia in the right eye [14].…”
Section: Eyesmentioning
confidence: 48%
See 2 more Smart Citations
“…We had 4 patients who had abnormal movements related to the eyes: one patient each of bilateral ptosis, blepharospasm, eyebrow dyskinesia, and bilateral 'painful' eyelid myoclonus. In a large series of 101 patients clinical examination triggered facial and eye movement disorders in 46% of patients, but, this phenomenon was not observed in any of our patients [15]. In the same vein, Stone et al in 2010 reported a case with recurrent episodes of right "pseudoptosis" with contraction of orbicularis oculis and oris which gave an impression of right facial weakness with unilateral photophobia in the right eye [14].…”
Section: Eyesmentioning
confidence: 48%
“…Depression and headache were also common in the series by Fasano et al [7]. Other organic clinical entities that were found to co-exist in 15 Certain limitations should be kept in mind before the interpretation of the results of our study. The major limitation was represented by its retrospective chart review design, which Video: Cranial functional movement disorder patients (cases 1-9): Abnormal movements, variability and distractibility are seen in different patients.…”
Section: Associated Illnessesmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies have also reported the presence of abnormal eye and cranial movements provoked by neurological examination (movement) [ 14 , 15 ] and functional seizures induced by photic stimulation, saline injections and hypnosis [ 5 ]. Such triggers have been also described in other neurological diseases like migraine [ 16 ], epilepsy [ 17 ], and Parkinson’s disease [ 18 ], but they have never been extensively investigated and characterized in FMD.…”
Section: Introductionmentioning
confidence: 99%
“…For the review of positive signs, we summarized in table 2 and table 3 those which had some form of validation (controlled designs to test for specificity and sensitivity or data on inter-rater reliability). To this end, we selected 22 studies45464748495051525354555657585960616263919293 reporting on 37 bedside clinical tests or groups of tests for motor FND (functional weakness and functional movement disorder) as well as 27 studies646566676869707172737475767778798081828384858687909495 reporting on 23 bedside clinical tests or group of tests for seizure type FND. In addition, we also discuss important case series or reviews that highlight relevant bedside clinical tests.…”
Section: Incidence and Prevalence Of Fndmentioning
confidence: 99%